2021
DOI: 10.3390/polym13040658
|View full text |Cite
|
Sign up to set email alerts
|

Role of Doping Agent Degree of Sulfonation and Casting Solvent on the Electrical Conductivity and Morphology of PEDOT:SPAES Thin Films

Abstract: Poly(3,4-ethylenedioxythiophene) (PEDOT) plays a key role in the field of electrically conducting materials, despite its poor solubility and processability. Various molecules and polymers carrying sulfonic groups can be used to enhance PEDOT’s electrical conductivity. Among all, sulfonated polyarylether sulfone (SPAES), prepared via homogenous synthesis with controlled degree of sulfonation (DS), is a very promising PEDOT doping agent. In this work, PEDOT was synthesized via high-concentration solvent-based em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…According to the results, as the amount of solvent increases, the size of the PEDOT:PSS polymer agglomeration decreases and the overall distribution becomes uniform. Consequently, the conductive PEDOT particles are uniformly distributed and the connection between the chains of the neighboring PEDOT polymers is enhanced so that the electrical conductivity increases [9,16,22]. These morphological analysis results are in good agreement with the chemical analysis results, which showed that the PEDOT polymer structure changes to a linear or expanded coil shape.…”
Section: Morphological Analysis Of Conductive Pastesupporting
confidence: 82%
See 2 more Smart Citations
“…According to the results, as the amount of solvent increases, the size of the PEDOT:PSS polymer agglomeration decreases and the overall distribution becomes uniform. Consequently, the conductive PEDOT particles are uniformly distributed and the connection between the chains of the neighboring PEDOT polymers is enhanced so that the electrical conductivity increases [9,16,22]. These morphological analysis results are in good agreement with the chemical analysis results, which showed that the PEDOT polymer structure changes to a linear or expanded coil shape.…”
Section: Morphological Analysis Of Conductive Pastesupporting
confidence: 82%
“…Additionally, the weak mechanical properties can also be improved by mixing or hybridizing the conducting polymer with general-purpose binders [6]. In addition, the electrochemical properties of the conducting polymer can be controlled or improved through synthesis with various organic solvents [8,9,16].…”
Section: Materials For Conductive Pastementioning
confidence: 99%
See 1 more Smart Citation